Pengaruh Pembiayaan Mudharabah Terhadap Profitabilitas pada PT Bank Syariah Indonesia KCP Pacitan - Mashithoh Fithri Azzahra; Subkhan Alimuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to analyze the impact of Mudharabah funding on profitability at PT Bank Syariah Indonesia KCP Pacitan. Mudarabah financing as the main product of Islamic banking business gives customers the opportunity to grow their business and contribute to the bank. In this study, the data used included financial degrees and information on Mudaraba fundraising from 2021 to 2025. This research method uses a quantitative approach using secondary data analysis of bank degrees and primary data received in management and customer interviews. The analysis method used is linear regression to measure the effectiveness of Mudaraba financing on profitability. The results of this study are expected to provide a clear understanding of the impact of Mudarabah financing on bank profitability and how strong the strengthening of strategy recommendations for managing PT Bank Indonesia KCP Pacitan in improving financial performance and business development.